2004
DOI: 10.1016/s0377-2217(03)00263-7
|View full text |Cite
|
Sign up to set email alerts
|

GRASP for set packing problems

Abstract: The principles of the Greedy Randomized Adaptative Search Procedure (GRASP) metaheuristic are instantiated for the set packing problem. We investigated several construction phases, and evaluated improvements based on advanced strategies. These improvements include a self-tuning procedure (using reactive GRASP), an intensification procedure (using path relinking) and a procedure involving the diversification of the selection (using a learning process). Two sets of various numerical instances were used to perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 18 publications
1
51
0
2
Order By: Relevance
“…In this section, we report the outcomes of testing the MN/TS algorithm on the set of 16 structured instances derived from the set packing problem [9,1], which have sizes ranging from 1000 to 2000. In [1], the set packing problem is solved via a unconstrained quadratic formulation while in [9], a dedicated GRASP heuristic was used.…”
Section: Computational Results On Structured Instances From Set Packingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we report the outcomes of testing the MN/TS algorithm on the set of 16 structured instances derived from the set packing problem [9,1], which have sizes ranging from 1000 to 2000. In [1], the set packing problem is solved via a unconstrained quadratic formulation while in [9], a dedicated GRASP heuristic was used.…”
Section: Computational Results On Structured Instances From Set Packingmentioning
confidence: 99%
“…In [1], the set packing problem is solved via a unconstrained quadratic formulation while in [9], a dedicated GRASP heuristic was used. For the approach to convert a set packing problem into a maximum weight independent set problem, interested readers are referred to [18].…”
Section: Computational Results On Structured Instances From Set Packingmentioning
confidence: 99%
“…Several studies have shown that GRASP produces good quality solutions for hard combinatorial optimization problems, particularly the set covering problems (Feo and Resende, 1995), the node packing problems (Feo et al, 1994) and the set packing problems (Delorme et al, 2004). Due to the fact that ALBPs can be seen as a special packing problem, we selected GRASP algorithm expecting a good behaviour of this search strategy when facing this kind of problem.…”
Section: Grasp Methodsmentioning
confidence: 99%
“…The heuristic proposed by Delorme et al (2004) was chosen to solve this SPP, first, because it generates several solutions with the same objective value, which is necessary to compare their stability, and, second, because this is one of the best published heuristics for the SPP according to the recent paper of Alidaee et al (2007).…”
Section: An Example Of Stability Evaluationmentioning
confidence: 99%